2016
DOI: 10.1002/tesj.272
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap: Student Attitudes Toward First Language Use in Monolingual EFL Classrooms

Abstract: This article challenges the widely held assumption in monolingual English as a foreign language (EFL) settings that students prefer their teachers to rarely use their mother tongue (MT)the language children initially learn in order to communicate. Through an examination of data derived from eight classrooms in four private language schools in Cyprus, the author identifies 16 speech acts performed by the students' exploitation of the first language (L1)-MT and L1 are used interchangeably-and unveils the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Learners' responses to the open-ended questions indicated that the main advantage of the use of L1 was that it helped them comprehend the lessons and vocabulary. The main disadvantage was that rely mostly on their L1, a sensible argument also found in other studies (see Ellis, 1984;Neokleous, 2016;Tsagari & Diakou, 2015;Tsagari & Georgiou, 2016) and a concern that was shared by the teachers participating in this study.…”
Section: Teachers' and Learners' Questionnairessupporting
confidence: 81%
See 2 more Smart Citations
“…Learners' responses to the open-ended questions indicated that the main advantage of the use of L1 was that it helped them comprehend the lessons and vocabulary. The main disadvantage was that rely mostly on their L1, a sensible argument also found in other studies (see Ellis, 1984;Neokleous, 2016;Tsagari & Diakou, 2015;Tsagari & Georgiou, 2016) and a concern that was shared by the teachers participating in this study.…”
Section: Teachers' and Learners' Questionnairessupporting
confidence: 81%
“…However, the teachers' attitudes and perceptions were wide-ranging, based on the learners' competency level and their learning requirements. Neokleous (2016), based on data derived from eight classrooms in four private language schools in Cyprus, challenged the widely held assumption in monolingual EFL settings that learners prefer their teachers to rarely use their L1. On the contrary, the participants perceived that L1 usage in the EFL classroom does not impose a learning constraint while the majority of the teachers highlighted its benefits and admitted the impossibility of alienating it from the classroom.…”
Section: Context Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This ideology of minimizing students' L1 was linked to the Grammar-Translation Method, which was believed to impede learners' opportunities to develop communicative competence because of the use of L1 (Neokleous, 2017). The later introduction of the Direct Method and Audio-Lingual Method emphasized the use of only TL, underlining that the use of L1 was a barrier to L2 learning and L2 oral proficiency development (Macaro, 1997).…”
Section: Using L1 As a Resource: A Literature Reviewmentioning
confidence: 99%
“…The use of L1, however, is a contested notion, in that many believe an ideal language learning and teaching environment is created in the TL, and L1 should have a minimal use-if not completely excluded (Macaro, 2001). Therefore, despite research indicating positive effects (e.g., Carroll & Morales, 2017;Neokleous, 2017;Vu, 2017), the use of L1 is hardly recognized in language-ineducation policies in most non-English speaking countries, and the monolingual ideologies are still dominant (Barnard & McLellan, 2014).…”
Section: Introductionmentioning
confidence: 99%